2010
DOI: 10.5194/adgeo-23-17-2010
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and temperature regime over Cyprus as a result of global climate change

Abstract: Abstract. In this study, the impact of global climate change on the temperature and precipitation regime over the island of Cyprus has been investigated. The analysis is based on daily output from a regional climate model (RCM) at a high horizontal resolution (25 km) produced within the framework of the EU-funded ENSEMBLES project. The control run represents the base period 1961–1990 and is used here as reference for comparison with future predictions. Two future periods are studied, 2021–2050 and 2071–2100. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 10 publications
(8 reference statements)
0
25
0
1
Order By: Relevance
“…For each crop, the ET and NIR estimates obtained using meteorological data across weather stations were not significantly different between the two 24-year periods. Taking into account the predictions for increased temperature and decreased precipitation in the region (Xoplaki et al 2004;Mizyed 2009;Milano et al 2012) and in Cyprus in particular (Price et al 1999;Pashiardis & Michaelides 2008;Giannakopoulos et al 2010), as well as the increased evaporation and ET predicted by a number of regional climate models (Giorgi & Lionello 2008;Lovelli et al 2010;Tanasijevic et al 2014), the present results could significantly assist decisions on future water management measures. Table 2.…”
Section: Discussionmentioning
confidence: 82%
“…For each crop, the ET and NIR estimates obtained using meteorological data across weather stations were not significantly different between the two 24-year periods. Taking into account the predictions for increased temperature and decreased precipitation in the region (Xoplaki et al 2004;Mizyed 2009;Milano et al 2012) and in Cyprus in particular (Price et al 1999;Pashiardis & Michaelides 2008;Giannakopoulos et al 2010), as well as the increased evaporation and ET predicted by a number of regional climate models (Giorgi & Lionello 2008;Lovelli et al 2010;Tanasijevic et al 2014), the present results could significantly assist decisions on future water management measures. Table 2.…”
Section: Discussionmentioning
confidence: 82%
“…The climate data restrictions result in local-scale studies which are limited to the use of point-data series. More studies can be found in the literature for the western part of our study region (Kostopoulou and Jones, 2005;Giannakopoulos et al, 2010;Kuglitsch et al, 2010;Hadjinicolaou et al, 2011). For instance, Kostopoulou and Jones (2005) studied possible changes in temperatureand precipitation-related climate extremes over the eastern Mediterranean region for the period 1958-2000.…”
Section: Introductionmentioning
confidence: 99%
“…The arid summer characteristics of the region have significant implications in several socioeconomic sectors. In the last few decades, Cyprus has been experiencing the worst water shortage on record (Giannakopoulos et al, 2010). The island covers a total of 9,251 km².…”
Section: Study Areamentioning
confidence: 99%